2014
DOI: 10.1021/cg5006659
|View full text |Cite
|
Sign up to set email alerts
|

Correction to Crystal Growth of Lysozyme Controlled by Laser Trapping

Abstract: On page 16, left column, second paragraph, first line, of this paper, the notation of sample of HEWL (Wako, >99.0%) is incorrect. The correct notation is as follows: HEWL (Wako, for Biochemistry).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…enhancement. We here should point out that the trend of growth rate change shown in Figure 4 is fully consistent with that in our previous work, 18 and these results are completely different than those on spontaneous growth with constant growth rate. Since such a considerably large SD for the mean G 101 and G 110 was still observed in this work, we carefully checked their temporal changes for each sample individually.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…enhancement. We here should point out that the trend of growth rate change shown in Figure 4 is fully consistent with that in our previous work, 18 and these results are completely different than those on spontaneous growth with constant growth rate. Since such a considerably large SD for the mean G 101 and G 110 was still observed in this work, we carefully checked their temporal changes for each sample individually.…”
Section: Resultssupporting
confidence: 91%
“…For temperature elevation by laser heating, we have already reported that little or no effect of the temperature elevation contributes to the crystal growth rate. 18 Furthermore, we also confirmed in this study that temperature elevation of a glass substrate by laser irradiation is negligible for the crystal growth rate. We carried out the same trapping experiment by replacing a glass substrate with a fused quartz slide showing a much lower absorption coefficient at 1064 nm.…”
Section: Crystal Growth and Designsupporting
confidence: 83%
See 2 more Smart Citations
“…40−42 By control of the laser polarization, the resultant crystal morphology is biased to certain forms. 41,42 The protein growth rate of lysozyme can be controlled by laser trapping, 43,44 amyloid fibril formation of cytochrome C can be spatiotemporally induced by laser trapping. 45 In general, the nanoparticles and molecules are trapped, concentrated at the focus, and distributed outside of the focus, giving their clusters, assemblies, and even crystals.…”
mentioning
confidence: 99%